SONGS AS A TOOL FOR PRONUNCIATION TEACHING - Abdug'aniyeva Durdona,; Zulfiya Axmedova, (TADQIQOTLAR, 2026)
Annotation: In recent years, the teaching of English pronunciation has received increasing  attention  as  a  crucial  component  of  effective  communication.  Accurate pronunciation not only enhances intelligibility but also boosts learners’ confidence and overall language competence. However, many learners face challenges in mastering pronunciation due to the complexity of English phonetics, differences from their native language, and limited exposure to authentic spoken input. Songs have emerged as an innovative  and  effective  tool  for  pronunciation  teaching.  They  provide  authentic language input in a natural and enjoyable context, exposing learners to rhythm, stress, intonation,  and  connected  speech.  Unlike  traditional  drills  and  repetitive  exercises, songs engage learners cognitively and emotionally, fostering both phonetic awareness and motivation. Singing along allows students to internalize pronunciation patterns subconsciously,  practice  fluency,  and  develop  a  more  natural-sounding  speech. Furthermore, songs facilitate social interaction, collaboration, and creative expression in the classroom, aligning with contemporary theories of language acquisition. They cater to different learning styles, activate multiple intelligences, and create a positive, low-anxiety learning environment. This makes songs a versatile pedagogical tool that not only improves pronunciation but also enhances learners’ overall engagement and enjoyment  in  the  language-learning  process.  This  study  aims  to  explore  the effectiveness of songs as a tool for teaching English pronunciation, focusing on their impact on learners’ phonetic development, motivation, and classroom interaction. The findings are expected to provide practical insights for educators seeking innovative and enjoyable strategies to improve pronunciation instruction.